Uniformly Dispersed Nano-SiO2 Particles Reinforced Copper Matrix by Chemical Coprecipitation Method. Issue 207 (3rd May 2020) - Bai, Yunlong; Li, Yulong; Wang, Jian; Fan, Wenji; Li, Zaiyuan; Fu, Yan; Lu, Yuhe; Wang, Wei
Abstract: Nano-Cu-based materials have many applications in the microelectronics and aerospace industries, which not only maintain the advantages of copper materials, but also make up for the shortage of copper. In this paper, the precursor powder of silica-reinforced copper matrix composites was prepared by chemical coprecipitation method, which main ingredients are Cu4 SO4 (OH)6 and SiO2 . The precursor powder was reduced by hydrogen in 450 °C for 4 h to obtain SiO2 -Cu composite powder, and then treated by cold press pressing and solid phase high temperature sintering to obtain nano-silica copper matrix composite. The results show that that the reinforcing phase and matrix are mutually dispersed in the process of coprecipitation, and the composite gains more homogeneous size and higher hardness as the dispersion effect of reinforcement on the copper matrix achieves the best.